(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
Speaking is one of the most important skills in language learning. However, many English as a Foreign Language (EFL) learners face difficulties in expressing their thoughts fluently and confidently. Group discussions have become an effective teaching strategy for developing speaking abilities because they provide students with opportunities to communicate, exchange ideas, and practice language in meaningful contexts. This article examines the role of group discussions in improving English speaking skills, analyzes their advantages, and suggests practical ways of implementing them in English language classrooms. The findings indicate that regular participation in group discussions enhances learners’ fluency, vocabulary, confidence, critical thinking, and communication competence.